PERAN EPISTEMOLOGI DALAM MENINGKATKAN KUALITAS PEMBELAJARAN DI SEKOLAH - Muhammad Rizky Fauzy; Daulat Saragi; Yacobus Ndona (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
ABSTRACT This study aims to examine the role of epistemology in improving the quality of learning in elementary schools. The problem addressed is the low quality of learning which tends to focus on knowledge transfer, resulting in students being less active and lacking critical thinking skills. This study employs a qualitative approach using a literature review method by analyzing various sources such as books, scientific journals, and relevant articles related to epistemology and learning. Data collection was conducted through documentation, while data analysis used content analysis techniques. The results indicate that epistemology plays a significant role as a foundation in understanding the nature of knowledge, sources of knowledge, and the process of acquiring and validating knowledge. The application of epistemology in learning encourages a shift from teacher-centered to student-centered learning. In addition, epistemology contributes to the development of students’ critical, reflective, and analytical thinking skills through a constructivist approach. The implication of applying epistemology is the creation of more active, meaningful, and contextual learning. Therefore, the integration of epistemology in learning is a strategic effort to improve the quality of education in elementary schools. Keywords: epistemology, learning quality, critical thinking, constructivism, elementary school